"Career Explorations? Sole Support Mothers Speak" - Bortolotto, Kim (My University, 2008)
Sole support mothers have received considerable attention by the federal government over the past 20 years, as they have been perceived as a burden on the social welfare system. Employment-related support programs have been designed to help single mothers transition into the workplace in order to become economically self-reliant and less dependent on the state. This feminist qualitative research study explored the barriers single-parent mothers experienced and the strengths they possessed in their attempts at re-entering the workforce 4 months after graduating from a Career Explorations program. The findings revealed that sole support mothers encounter multiple barriers upon entering the job market including: difficulty with balancing family life responsibilities with obtaining an income, negative attitudes and stigma held by society and employers towards single mothers, lack of recognition of job skills, low wages and ethnic discrimination. A positive attitude, spiritual faith and the ability to perform one's job well were factors that contributed to the women's efforts and resiliency at securing work. Both study participants expressed their views regarding single mothers as being a "unique group of individuals" with "specialized needs." Recommendations for programs included the development of a "coffee house" designed specifically for single mothers where they can gain support and learn from the successes of other single mothers. The study concludes with a review of the implications for social work practice and possibilities for future research.
Keywords: Social Work; Social Work